2016
DOI: 10.2135/cropsci2015.06.0383
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Alternatives for Chromosome Doubling in Maize Haploids for Doubled‐Haploid Production

Abstract: In vivo production of doubled‐haploid (DH) lines in maize (Zea mays L.) routinely involves artificial chromosome doubling by colchicine treatment of seedlings. Because colchicine is a hazardous chemical, replacing it by less‐toxic alternatives would be highly desirable. Our objectives were to (i) test the efficacy of various herbicides alone or in combination with other herbicides or phytohormones as chromosome doubling agents, (ii) evaluate the efficacy of application of these chemicals for different duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 27 publications
2
82
0
Order By: Relevance
“…The observed spontaneous chromosome doubling rate of 52% of this study is at the lower end of the 50-80% range reported in literature (Olesen et al 1988;Bante et al 1990;Halberg et al 1990;Begheyn et al 2016b). Besides spontaneous polyploidization, chromosome doubling may also be induced by in vitro or in vivo application of chromosome doubling agents such as colchicine (Melchinger et al 2016;Ślusarkiewicz-Jarzina et al 2017). In contrast to triticale (Lantos et al 2014) and wheat (Rubtsova et al 2013) however, this is not considered necessary in perennial ryegrass due to a high level of natural chromosome doubling (Andersen et al 1997).…”
Section: Robustness Of Androgenic Capacitymentioning
confidence: 46%
“…The observed spontaneous chromosome doubling rate of 52% of this study is at the lower end of the 50-80% range reported in literature (Olesen et al 1988;Bante et al 1990;Halberg et al 1990;Begheyn et al 2016b). Besides spontaneous polyploidization, chromosome doubling may also be induced by in vitro or in vivo application of chromosome doubling agents such as colchicine (Melchinger et al 2016;Ślusarkiewicz-Jarzina et al 2017). In contrast to triticale (Lantos et al 2014) and wheat (Rubtsova et al 2013) however, this is not considered necessary in perennial ryegrass due to a high level of natural chromosome doubling (Andersen et al 1997).…”
Section: Robustness Of Androgenic Capacitymentioning
confidence: 46%
“…The haploid genome doubling rate of trifluralin treatment in B. napus was 85.7%, for colchicine 74.1% and for oryzalin 66.5%, compared to only 42.3% without any treatment (KlíMa et al ., ). APM combined in an optimum dosage with pronamide has similar rates of genome doubling as colchicine in maize (Melchinger et al ., ). Kato and Geiger () developed an effective genome doubling procedure in maize using a nitrous oxide (N 2 O) gas treatment at the six‐leaf stage, with about 44% of the haploids producing seed after selfing.…”
Section: Genome Doublingmentioning
confidence: 97%
“…The plant materials for Exp. 2 and 3 (Table S1) were taken from experiments reported in previous papers (Melchinger, Molenaar et al, ; Molenaar et al, ) on alternative methods for production of DH lines (for details see section on treatments) so that H, DH and C plants could be evaluated as in DH production, but using chemically induced chromosome doubling agents (Table S2). In both experiments, the rate of false positives, measured as the proportion of C plants in the total number of plants surviving from putative haploid seeds until flowering time, was within the normal range (3.04%–27.7%) encountered in DH production of maize.…”
Section: Methodsmentioning
confidence: 99%
“…Improving the success rate of chromosome doubling and replacing the routine treatment with colchicine by simpler and cheaper methods could be an alternative avenue to reduce the costs of DH production (Melchinger, Molenaar, Mirdita, & Schipprack, ). However, research on this step requires measuring the success rate of different treatments, which currently entails cultivating the treated plants for a whole season and evaluating the seed set of the selfed D 0 plants.…”
Section: Introductionmentioning
confidence: 99%